The Clinical Development Program of Lixisenatide: A Once-Daily Glucagon-Like Peptide-1 Receptor Agonist - Bain, Stephen C. (Diabetes Ther, 2014)
Lixisenatide (AVE0010) is a once-daily glucagon-like peptide-1 (GLP-1) receptor agonist used in the treatment of type 2 diabetes. Phase II dose-finding and pharmacodynamic studies identified the 20 µg once-daily dose as having the optimum combination of efficacy, convenience and tolerability. Lixisenatide was prospectively investigated in a series of 11 multinational, randomised, controlled phase III trials (GLP-1 agonist AVE0010 in paTients with type 2 diabetes mellitus for Glycemic cOntrol and sAfety evaLuation [GetGoal] programme) that included a direct head-to-head study with exenatide. The GetGoal programme established the efficacy and safety profile of lixisenatide 20 µg once daily across the spectrum of patients with type 2 diabetes, including patients not treated with anti-diabetic agents, those failing on oral agents and as an adjunct to basal insulin therapy. The main efficacy endpoints were met in all studies, with the baseline to endpoint reductions in HbA(1c) consistently ranging from 0.7% to 1.0%. In a head-to-head comparison with exenatide 10 μg twice daily, lixisenatide 20 μg once daily was non-inferior for HbA(1c) reduction, achieved with threefold fewer patients with symptomatic hypoglycemia events and better gastrointestinal tolerability. Three randomised trials of lixisenatide treatment added to basal insulin showed significantly improved glycemic control over placebo, with pronounced postprandial glucose reductions and good tolerability. Discontinuations for adverse events were consistently low, ranging from 2.5% to 10.4%. As the provision of individualized care moves center stage in diabetes management, lixisenatide with once-daily dosing, a single maintenance dose and fixed-dose pens offers an important treatment option for type 2 diabetes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13300-014-0073-z) contains supplementary material, which is available to authorized users.